Comparative evaluation between oral gabapentin and oral pregabalin premedication for attenuation of hemodynamic surge to laryngoscopy and endotracheal intubation in elective procedures under general anesthesia - Dubey, Kunal Chandra; Bajpai, Nupur; Richeek Kumar Pal; Chattopadhyay, Subhrajyoti; Sah, Sunil Kumar; Sarkar, Susanta (Asian Journal of Medical Sciences, 2024)
Background: Effective attenuation of the sympathetic surge due to laryngoscopy and endotracheal intubation is needed. We wanted to compare the role of oral gabapentin (600 mg) and oral pregabalin (150 mg) in controlling this sympathetic surge. Aims and Objectives: To compare the role of oral gabapentin (600 mg) and oral pregabalin (150 mg) as premedications for attenuating hemodynamic surge to laryngoscopy and endotracheal intubation. Materials and Methods: 90 patients aged 18–45 years with ASA grade I or II posted for elective surgical procedure under general anesthesia were randomly allocated to two equal groups (45 in each group) to receive either 600 mg oral gabapentin or 150 mg oral pregabalin 1 h prior to surgery. Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and rate pressure product (RPP) were recorded after intubation at 1 (T1), 3 (T3), 5 (T5), and 10 (T10) min. Post-operative sedation and post-operative nausea and vomiting (PONV) were recorded and compared. Results: Gabapentin attenuates hemodynamic surge in terms of HR, SBP, DBP, MAP, and RPP better than pregabalin during laryngoscopy and endotracheal intubation at 3, 5, and 10 min after intubation, while there was no significant difference between the two groups at 1 min after intubation. Post-operative sedation score and adverse effects like PONV and SpO2 fluctuations at different points in time were comparable. Conclusion: Oral gabapentin (600 mg) was found to be more effective than oral pregabalin (150 mg) in attenuating the hemodynamic surge to laryngoscopy and intubation.